2017
DOI: 10.3892/mco.2017.1468
|View full text |Cite
|
Sign up to set email alerts
|

Role of endometriosis as a prognostic factor for post‑progression survival in ovarian clear cell carcinoma

Abstract: Abstract.The clinical significance of coexistence of endometriosis (EM) in ovarian clear cell carcinoma (CCC) has not yet been determined. The aim of the present study was to analyze the correlation of endometriosis with clinicopathological factors in CCC. The cases with CCC that received primary debulking surgery at the present hospital between 1990 and 2013 were identified. Retrospective analysis was conducted to evaluate the association between complications with EM and clinicopathological features in CCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Moreover, the mechanism of action underlying the effect of SMYD2 on cell proliferation and apoptosis, including the potential role of p53 methylation, has not been addressed. Lastly, endometriosis is reportedly a precursor of OCCC (34), and therefore analysis of SMYD2 expression in OCCC should be compared with normal ovarian tissues as well as with tissues of endometriosis in the future. Nevertheless, the present findings suggest that SMYD2 increases the proliferation of OCCC cells in vitro, suggesting a potential therapeutic avenue for SMYD2 inhibition in the treatment of OCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mechanism of action underlying the effect of SMYD2 on cell proliferation and apoptosis, including the potential role of p53 methylation, has not been addressed. Lastly, endometriosis is reportedly a precursor of OCCC (34), and therefore analysis of SMYD2 expression in OCCC should be compared with normal ovarian tissues as well as with tissues of endometriosis in the future. Nevertheless, the present findings suggest that SMYD2 increases the proliferation of OCCC cells in vitro, suggesting a potential therapeutic avenue for SMYD2 inhibition in the treatment of OCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies concluded that presence of endometriosis was not a prognostic factor, [15,33,34] others reported that endometriosis was an independent predictor of better survival [35] or worse survival. [36] However, one should note that many studies comparing survival of OCCC with or without endometriosis did not draw a clear distinction between cancer with coexisting endometriosis and cancer arising from endometriosis. As these may be 2 different subgroups of OCCC, the results of these studies should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…The association of endometriosis and ovarian cancer has been widely reported 43 , 44 . Between 18% and 43% of women with OCCC have a history of endometriosis 19 , 45 - 48 , and several studies have demonstrated that this benign disease is a precursor lesion of OCCC and endometrioid carcinoma 21 .…”
Section: Pathogenesis Of Occcmentioning
confidence: 99%
“…Moreover, endometriosis was found to be associated with amplification of epidermal growth factor receptor (EGFR) gene and the activation of EGFR plays a critical role in cell proliferation, apoptosis, angiogenesis, and metastasis 16 , thus it is necessary to identify whether the amplification of EGFR can trigger the progression from endometriosis to carcinoma. The risk of tumorigenesis in endometriosis is about 1% among premenopausal women and 1% to 2.5% among postmenopausal women 45 , 53 . The risk for 20-year-old women is considered to be 1.00, therefore the risks for women in their 40s and 50s are 3.60 and 10.7, respectively, which indicates that the tumorigenesis of endometrial cysts occurred around menopause 54 .…”
Section: Pathogenesis Of Occcmentioning
confidence: 99%
See 1 more Smart Citation